2007
DOI: 10.1093/pubmed/fdm020
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative attendance, assessment and cancer detection rate over four screening rounds in five English breast-screening programmes: a retrospective study

Abstract: Current monitoring shows constant uptake over time, but when looking at a cohort of individual woman, a much larger percentage have 'ever' attended and a smaller number have attended all invitations. The chance of a woman being assessed at all, if she attends all four rounds, is 12.3%, which can be calculated by summating the recall rates in each round.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…This is higher than the cumulative false-positive rates over 10 screens of 8-21%, predicted on the basis of 3-5 screening rounds in women aged 50 to 69 in Denmark (19), and higher than the 21% risk over 20 years of biennial screening for women aged over 50 in Norway (20). The Age trial rate is also higher than the 10-11% cumulative false-positive rate estimated from NHSBSP cancer detection and cumulative assessment rate data for four screening rounds at five units published by Wallis et al (21). However, the Age trial rate is significantly lower than most reported rates for US women aged under 50 which are of the order of 34% after five screens for women aged 40-49 (22).…”
Section: Discussionmentioning
confidence: 58%
“…This is higher than the cumulative false-positive rates over 10 screens of 8-21%, predicted on the basis of 3-5 screening rounds in women aged 50 to 69 in Denmark (19), and higher than the 21% risk over 20 years of biennial screening for women aged over 50 in Norway (20). The Age trial rate is also higher than the 10-11% cumulative false-positive rate estimated from NHSBSP cancer detection and cumulative assessment rate data for four screening rounds at five units published by Wallis et al (21). However, the Age trial rate is significantly lower than most reported rates for US women aged under 50 which are of the order of 34% after five screens for women aged 40-49 (22).…”
Section: Discussionmentioning
confidence: 58%
“…There also appears to be a difficulty in ensuring continuity of uptake in the South Asian population, especially among Muslim women. Global figures which show a decreasing gap in breast cancer screening uptake over time between South Asian women and the majority population [7] might therefore mask differences in the continuity of uptake [34]. Just under half (45.6%) of Muslim women who undertook mammography in round 1 decided not to participate in both of rounds 2 and 5, mainly choosing instead to participate in just one of the two subsequent rounds.…”
Section: Discussionmentioning
confidence: 99%
“…12 In the Age trial, 18.7% of the intervention arm (10,092 women) failed to attend any of the routine annual screening invitations they were offered. A study by Wallis et al 13 covering a cohort of women invited by the NHSBSP over a similar time period, but looking at four three-yearly screening rounds, found 10% of women failed to attend any screens. The same study reported that 62% of women attended all four screens and 77% attended three of the four offered screens.…”
Section: Discussionmentioning
confidence: 99%